Hasil Musyawarah Keagamaan Kongres Ulama Perempuan Indonesia I dalam Sudut Pandang Ekonomi - Muheramtohadi, Singgih (Sawwa: Jurnal Studi Gender, 2018)
Economic point of view is needed to view all human activities on the effort to meet the needs or profit collection. On this paper, economic approach to view the three big issues was resulted by the conference in Indonesia’s First Female Muslim Clerics Congress in Cirebon. These three issues consist of sexual violence, child marriage, and natural damage. In these conferences, view these three big problems in Islamic teaching. This paper tries to view these problems in economic basic view. The three big problems not only the problem of ethic merely these about the economic problem because the economic factors play a big role in these problems. This paper will discuss the problems with the description of the result of the conference, and analyze it with an economic approach. Mostly the destroyers of the environment are motivated by economic behavior. Economic behavior also plays a role in most of the child marriage cases and in many of sexual violence cases.